Naturalness - Cvetko-Orešnik, Varja (Linguistica (Ljubljana), 2011)
The framework of the paper is Natural Syntax initiated by Janez Orešnik in thetradition of (morphological) naturalness as established by Wolfgang U. Dressler and Willi Mayerthaler. The basic tenets of Natural Syntax are described at the beginning of the paper. Natural Syntax is here applied to aspects of Old Indian synchronic verbal morphonology and verbal morphosyntax: (1) Causative -áya- verbs in Rig Veda and Atharva Veda. The root vowel a is short in closed syllables and long in open syllables. (2) Rig Veda and Atharva Veda contain 31 intransitive and 175 transitive -áya- verbs. (3) Rig Veda and Atharva Veda do not contain any causative verbs to the basic transitive verbs. (4) Post-Vedic double transitive verbs (the early construction) contain an obligatory accusative corresponding to the subject of the base verb, and an optional accusative corresponding to the object of the base verb. (5) Post-Vedic double transitive verbs (the late construction) contain an obligatory instrumental corresponding to the subject of the base verb, and an accusative corresponding to the object of the base verb. (6) The accusative mentioned in (5) is not obligatory. The data have been taken from Jamison (1983), a monograph about Old Indian -áya- verbs.
Keywords: glagol; morphosyntaxe naturelle; naravna oblikoskladnja; naravna skladnja; skladnja; stara indijščina; syntax; syntaxe; syntaxe naturelle; teorija jezikovne naravnosti; théorie du langage naturel; verb; vieil indien